SUSTAINABLE LIVELIHOOD AND SUSTAINABLE DEVELOPMENT: THE EXPERIENCE OF COLLECTIVE FARMING BY KUDUMBASHREE IN KERALAM, INDIA - Kumaramkandath, Rajeev; Verghese, Bindu P. (UI Scholars Hub, 2016)
One of the most alarming impacts of development experienced by Third world economies in the contemporary era of globalization is the fast depletion of agricultural land. This is especially so in countries in the Third world where the rapidly increasing population and unplanned growth of economies have decreased the size of croplands to highly threatened levels. There has also been a significant shift in the meaning of land in several of these locations to being an object that can be sold and bought like any other commodity. Looking at it from a wider perspective one can vividly see that all harmful impacts – ranging from shortage of food production to global warming – of development have basically arisen from the shifts in the meaning and uses of land. The context of Keralam in South India is not an exemption from these trends, where, in fact, they have more intense connotations due to the small size of its geography and the heavy density of population – high even by the standards of developing economies. The state, once known for high levels of social development, has switched its focus towards economic development from mid 1990s. This has resulted in a real estate boom in the state where there is a huge demand for land for the purposes of erecting shopping malls, residential complexes and so on. One dangerous outcome of this was that most of the land thus sold was fertile paddy fields, which play a central role in ground water conservation as well as in sustaining its rich biodiversity. The changing equations over land and its utility have considerably contributed to the changing ecological balances within the region. The need to reinvent sustainable forms of development specific to the conditions of the state was felt acutely amidst such transformations. There was a sudden demand to reinvent the productive capacity of land, especially paddy fields, in the state by both involving more people in this area as well as by resuming farming in land that otherwise remain fallow waiting for real estate agents. Kudumbasree was an organization that commenced its operations in the State in 1998 with the intention of engaging in women empowerment and poverty alleviation programmes. Its successful career has motivated its workers, basically housewives and women from different walks, to focus on non-traditional sectors in the state. As part of this, Kudumbashree started to intervene in the agriculture sector in 2002 with the objective of ensuring sustainable livelihood to poor families by bringing back fallow land to cultivation and women to agriculture. This was the context against which the idea of collective farming was introduced by the organisation. This not only ensured a new, albeit unconventional, and sustainable source of livelihood for women in the community but also has been considerably contributing to food and nutritional security of the state. This has literally revolutionized the development concepts in the society where women empowerment and livelihood programmes were combined to reinvent the idea of sustainability.